Double-Porosity in Soil - Ngien, Su Kong (Springer Nature, 2023)
This image shows inter-aggregate and intra-aggregate pores, one of the double-porosity phenomena that may exist in soil. Double-porosity occurs in soil when two sets of porosities having highly contrasting hydraulic properties co-exists in the fabric of the soil.